Echinococcosis New Perspectives - Inceboz, Tonay (Infectious Diseases, 2023)
Echinococcosis is a neglected parasitic disease caused by Echinococcus spp. of the family Taeniidae. The prevalence of the disease is increasing worldwide due to industrialization and climate change. This book provides a comprehensive overview of echinococcosis, including information on epidemiology, geographic distribution, diagnosis, management, and prevention.